Clove Extract and Grape Seed Oil Nanoemulsion for Oral Diseases Therapy: Antibacterial and Antioxidant Activities - Hartati, Julia; Damayanti, Meta Maulida; Nur, Ismet Muchtar; Furqaani, Annisa Rahmah; Sari, Ajeng Kartika; Rachmawati, Meike; Siddiq, Tita Barriah; Fakih, Taufik Muhammad; Radina, Faqih (Global Medical & Health Communication (GMHC), 2023)
The growth of micro-organisms that acquire resistance to most commercially available antibiotics is occurring rapidly. Consequently, a pressing necessity exists to identify and detect new antimicrobial substances. This study aimed to analyze the antioxidant and antibacterial activity of nanoemulsion clove extract and grape seed oil. This research was conducted in June 2023 using experimental methods at the Research Laboratory of the Universitas Islam Bandung Pharmaceutical Study Program by developing a nanoemulsion preparation containing clove extract (Syzygium aromaticum L.) and grape seed oil (Vitis vinifera L.). Antioxidant activity was tested using the 2,2-diphenyl-1-picrylhydrazyl (DPPH) method. Antibacterial activity was tested using the agar diffusion method by measuring the growth inhibitory diameter of Staphylococcus aureus and Streptococcus mutans bacteria and divided into four groups formulas based on the addition of clove extract with different concentrations in the nanoemulsion base (FA=0.25%, FB=0.5%, FC=0.75%, and FD=1%) to see the best results. The result shows nanoemulsion preparations have antioxidant properties in the DPPH test. The FA formula has the highest IC50, namely 1,117.56 ppm. The antibacterial activity of Staphylococcus aureus and Streptococcus mutans has an inhibition zone, although it is still in the category of inhibiting bacterial growth, but does not kill growth. The nanoemulsion formulation, comprising clove extract and grape seed oil, has exhibited exceptional antioxidant properties and substantial antimicrobial efficacy against prevalent oral bacterial strains.